Peran Budaya 5S (Salam, Senyum, Sapa, Sopan, Santun) Dalam Pembentukan Karakter Siswa Melalui Pendekatan Kontruktivisme Di MI An-Nur - Naufal Failasuf; Anisatun Muthi’ah Husein; Nur Muhammad Ainul Hayat; Eliya Agustin; Tis’atun Hasanah; Bagus Mahardika (PT. Nawa Edukasi Nusantara, 2025)
Waste management remains a serious environmental issue in various regions, including Islamic boarding schools (pesantren). The low level of public awareness and participation in waste management demonstrates the need for an educational approach that is not only technical but also social and cultural. This study aims to analyze the application of the Zone of Proximal Development (ZPD) concept in community-based waste management education at the Krapyak Peduli Sampah Community, Ali Maksum Islamic Boarding School, Krapyak, Bantul. This study used a descriptive qualitative approach with observation, interviews, and documentation methods. Data analysis was carried out through the stages of data reduction, data presentation, and conclusion drawing. The results show that the application of the ZPD principle through social interaction, mentoring between residents, and practice-based learning can increase awareness, skills, and participation of students in waste management. The learning process takes place collaboratively through guidance from senior students, Islamic boarding school administrators, and reinforcement of local religious and cultural values. These findings indicate that a community-based sociocultural approach is effective in developing sustainable ecological behavior. Thus, the application of the ZPD concept can be a relevant educational strategy in community-based waste management.